2019
DOI: 10.1186/s12879-019-4298-3
|View full text |Cite
|
Sign up to set email alerts
|

Fecal carriage and molecular epidemiology of carbapenem-resistant Enterobacteriaceae from outpatient children in Shanghai

Abstract: Background Fecal colonization with carbapenem-resistant Enterobacteriaceae (CRE) is a risk factor for bacterial translocation resulting in subsequent endogenous infections. The purpose of this study is to investigate the prevalence of CRE strains colonization in stool samples of outpatient in a tertiary pediatric hospital of Shanghai, China. Methods In a retrospective study, fecal samples were consecutively obtained from patients in 2016 and screening test for CRE was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
31
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 34 publications
13
31
1
Order By: Relevance
“…These factors are considered as risk factors in the occurrence of CRKP in previous studies. [30][31][32] In addition, a significant portion of strains were obtained from blood specimens, suggesting that CRKP bloodstream infection was a major problem in this study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These factors are considered as risk factors in the occurrence of CRKP in previous studies. [30][31][32] In addition, a significant portion of strains were obtained from blood specimens, suggesting that CRKP bloodstream infection was a major problem in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, NDM-1-producing CRKP was resistant to them, which were agreed with another report. 32 Interestingly, a study showed that NDM-5-producing KP strains have high resistance to quinolones, 35 while, other studies proposed controversial points. 10,13 Hence, the diversity of carbapenemases among CRKP strengthens the difficulty for infection control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly fecal carriage of MDR major ST K. pneumoniae strains were reported from various continents in both outpatients and the general population with higher prevalence in developing countries (Zhang et al, 2015;Baraniak et al, 2016;Aghamohammad et al, 2018;Büdel et al, 2019;Pan et al, 2019). In addition, most recently MDR major ST strains of K. pneumoniae were observed to colonize more frequently the respiratory system than the gastrointestinal tract (Shu et al, 2019).…”
Section: The Virulence Component In Mdr K Pneumoniaementioning
confidence: 99%
“…Colonization of multidrug resistant bacteria in the gastrointestinal tract may be a risk factor for bacterial translocation, leading to endogenous infections in immunocompromised children [6]. Colistin resistance is considered of special clinical signi cance in the Enterobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%